THE MODELING OF DYNAMIC PROCESSESIN THE TRACTION DRIVES OF LOCOMOTIVES FOR DIFFERENT OPERATIONAL MODES - Kiiko, A. I. (Science and Transport Progress, 2004)
The article represents some results of computer modelling of dynamic processes in the tractive drive of freight and passenger electric locomotives in realization of marginal friction forces and their interaction with anti-boxing system of boxing prevention.